Diseño de un Banco para Programación de un Controlador Lógico Programable (PLC) Marca DELTA. (2023)
Currently, the company doesn´t have a "console" module for basic, medium and advanced level learning for engineers in the subject of programmable logic programming "PLC". During the time of work, it has been shown that the training and projects are executed by the project manager, causing his work and his scope within the company to be delayed and we don´t have greater coverage in the company's projects. With the design of this module it is intended that the company make the investment for the construction of the module and the engineering department is able to automate the processes of our clients. Currently there are 5 project engineers and 20 electrical technicians. With this staff capacity, an average of 10 pieces of equipment per month are currently installed.